Reliability of Magnetic Resonance Imaging Prediction of Anterior Cruciate Ligament Autograft Size and Comparison of Radiologist and Orthopaedic Surgeon Predictions. Issue 12 (13th December 2019) - Hanna, Andrew; Hollnagel, Katharine; Whitmer, Kelley; John, Christopher; Johnson, Brent; Godin, Jonathan; Miller, Thomas
Background: In anterior cruciate ligament (ACL) reconstruction, hamstring tendon autografts <8 mm have been associated with increased failure rates. There has been no established modality by which orthopaedic surgeons can preoperatively predict graft sizes. Purpose/Hypothesis: The purposes of this study were to (1) determine whether routine magnetic resonance imaging (MRI) measurement of hamstring tendon cross-sectional area (CSA) can reliably be used by sports medicine fellowship–trained orthopaedic surgeons to predict graft size and (2) determine whether radiologists and sports medicine surgeons are able to discriminate grafts below a predetermined cutoff value. We hypothesized that radiologists will find a correlation between MRI measurement and intraoperative graft size. Similarly, orthopaedic surgeons will be able to correctly estimate the graft size based on MRI measurement. Study Design: Cohort study (diagnosis); Level of evidence, 2. Methods: Included in this study were 30 consecutive patients (15 women and 15 men) (mean age, 23 years [range, 13-43 years]) for whom MRI-determined hamstring tendon CSA and graft size measurements could be compared. Patients were included if they had a preoperative MRI demonstrating acute ACL rupture and were scheduled with 1 of 3 surgeons for a reconstruction performed using the ST and GR tendons. Operative data were collected over 1 year. Sectra imaging software was used to measure the CSA of the semitendinosus (ST) and gracilis (GR) tendons on the preoperative MRIs. Control measurements were performed intraoperatively using a graft sizing block with 0.5-mm increments. Simple linear regression analysis was used to evaluate the ability of MRI measurements to predict autograft size. Logistic regression was used to determine the minimum CSA for a graft of 8 mm. The intraclass correlation coefficient (ICC) was used to evaluate interrater reliability. Results: MRI CSA measurement of the average STGR (ST CSA added to the GR CSA) was a significant predictor of graft size (adjusted R 2 = 0.186; P < .001). The 3 measurements with the strongest correlations with graft size were the ST at the medial femoral condyle (MFC), the STGR at the MFC, and the average STGR. The minimum CSA for the average STGR on MRI to achieve a graft size of 8 mm was 17.168 mm 2 ( P < .001). The area under the receiver operating characteristic curve was 0.765. The overall ICC was 0.977. Conclusion: Routine preoperative MRI can be used by both radiologists and orthopaedic surgeons to predict the expected ACL autograft size and identify those below a cutoff of 8 mm. This will help in preoperative planning and graft selection.